2017
DOI: 10.1002/chem.201703255
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Rotamerism at the Origin of a Chessboard Supramolecular Assembly of Ruthenium Phthalocyanine

Abstract: We have investigated the formation and the properties of ultrathin films of ruthenium phthalocyanine (RuPc) vacuum deposited on graphite by scanning tunneling microscopy and synchrotron photoemission spectroscopy measurements, interpreted in close conjunction with ab initio simulations. Thanks to its unique dimeric structure connected by a direct Ru-Ru bond, (RuPc) can be found in two stable rotameric forms separated by a low-energy barrier. Such isomerism leads to a peculiar organization of the molecules in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Below, we will show a detailed close-up of the effects induced by the surface–molecule interaction as obtained by DFT simulations. However, before discussing the results of such an investigation on the electronic properties and the molecular assembling features of the three (RuPc) 2 –substrate systems, it is convenient to report some of the properties of an isolated molecule, already discussed in detail elsewhere. , As established in these previous studies, (RuPc) 2 can be found in two different conformers (rotamers) characterized by two different twist angles of the two organic ligands: in the semi-eclipsed rotamer, the N–Ru–Ru–N dihedral angles are around 18°/72°, and in the staggered rotamer, it is around 45° (see Figure a for the staggered structural model). The two rotamers are almost energetically degenerate and are separated by a shallow energy barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Below, we will show a detailed close-up of the effects induced by the surface–molecule interaction as obtained by DFT simulations. However, before discussing the results of such an investigation on the electronic properties and the molecular assembling features of the three (RuPc) 2 –substrate systems, it is convenient to report some of the properties of an isolated molecule, already discussed in detail elsewhere. , As established in these previous studies, (RuPc) 2 can be found in two different conformers (rotamers) characterized by two different twist angles of the two organic ligands: in the semi-eclipsed rotamer, the N–Ru–Ru–N dihedral angles are around 18°/72°, and in the staggered rotamer, it is around 45° (see Figure a for the staggered structural model). The two rotamers are almost energetically degenerate and are separated by a shallow energy barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Geometry optimization simulations have been performed by using the C09 gradient corrected functional together with an ab initio VDW-DF , method (C09+VDWDF). The C09+VDWDF method provides accurate description of the structural properties of noncovalent organic–inorganic interfaces. ,, The Kohn–Sham orbitals have been expanded on a plane-wave basis set, with core electrons replaced by ultrasoft pseudopotentials . Satisfactorily converged results have been achieved by using cutoffs of 40 Ry (320 Ry) on the plane waves (electronic densities).…”
Section: Methodsmentioning
confidence: 99%
“…Aggregation is a well-known property of phthalocyanines because of their planar aromatic system that likely stacks due to π-π interactions. [33][34][35] Hence, the shoulder at 653 nm, blueshifted with respect to the Q band maximum, can be ascribed to the cofacial H-type aggregation between molecules. As a matter of fact, the series of UV-Vis spectra at concentrations between 10 À 5 and 10 À 6 M reported in Figure 3 is coherent with such interpretation, being the absorption shoulder clearly and strongly dependent upon concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the Q band of ZnPc−(BTBT) 4 appears broadened because of significant aggregation effects that occur even in coordinating solvents, likely due to its wide and mostly planar conjugated structure. Aggregation is a well‐known property of phthalocyanines because of their planar aromatic system that likely stacks due to π–π interactions [33–35] . Hence, the shoulder at 653 nm, blueshifted with respect to the Q band maximum, can be ascribed to the cofacial H‐type aggregation between molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand phthalocyanine has been widely used in chemical dyes [36] and photoelectronic devices [37, 38]. Various metal encapsulated phthalocyanines, for example, CuPc [39], ZnPc [40], F 16 CuPc [41], RuPc [42], TiPc [43], NiPc [39], Li‐CuPc [39], and so forth, have been reported. Metallophthalocyanines (MPc's) have many potential applications in nanoparticle construction, photovoltaics, photodynamic therapy, and catalysis [44–46].…”
Section: Introductionmentioning
confidence: 99%